Comparative Analysis of Public Perception of Intention to Buy in Online Marketing and Offline Marketing (Study at Naqi Collection Ajamu Store) - Melin Syahfitri; Elida Florentina Sinaga Simanjorang; Muhammad Ali Al-Ihsan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to find out how the marketing strategy was carried out by the Naqi Collection Ajamu Shoe Store and to compare consumer buying interest in online marketing and offline marketing. Researchers used a qualitative approach with data collection techniques in the form of questionnaires which were distributed to consumers who had shopped at the Ajamu Naqi Collection Store. Data analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. From the results of the study, it can be concluded that offline marketing is more effective than online marketing, consumers are more interested in shopping directly at stores than ordering online. Online marketing run by Naqi Collection Ajamu Shop is not enough to attract consumers, because it posts pictures without accompanying them with clear specifications, this certainly raises doubts for consumers to make purchases online. Whereas in offline marketing, Naqi Collection Ajamu Shop is quite good, in terms of service and quality of goods to achieve customer satisfaction in making offline purchases.